Երկրների միջև լարվածության թուլացման ուղղված դիվանագիտական մեթոդների վերլուծություն - Պետրոսյան, Վարդուհի (ԱԵԳՄՄ հրատ.)
The purpose of the article is to highlight diplomatic methods the knowledge and application of which can significantly contribute to improving relations between countries and, in some cases, easing existing tensions. The article discusses the challenges diplomats face in achieving this goal, particularly in ensuring ongoing dialogue and fostering cooperation between nations. For a diplomat, understanding cross-cultural characteristics is especially crucial. This understanding helps them avoid tactless or offensive expressions or actions and, when used skillfully, leverage cultural nuances to benefit negotiations. The success of negotiations also hinges on a diplomat's personal qualities: personal charisma, pleasant demeanor, comprehensive mastery of the negotiation subject, profound expertise in global civilization and contemporary geopolitics, as well as proficiency in intercultural communication and related matters. The article employs methods such as critical analysis of current trends in bilateral and multilateral diplomacy, as well as simultaneous and cross-temporal examination of the subject matter. The primary conclusion drawn is that successful diplomatic endeavors require a blend of the aforementioned professional skills and essential personal qualities. Additionally, diplomats must effectively represent their country, both in private and public engagements. Цель статьи выделить дипломатические методы, знание и применение которых могут во многом способствовать улучшению отношений между странами, а в некоторых случаях и ослаблению существующей напряженности между странами. В статье обсуждаются задачи, стоящие перед дипломатами в достижении этой цели, а именно поиск путей обеспечения постоянного диалога и развития сотрудничества между странами. Для дипломата особенно важно знание межкультурных особенностей, позволяющее избегать бестактных или оскорбительных выражений или действий и при умелом использовании ‒ применять их во благо переговоров. Успех переговоров определяется также личными качествами дипломата: личной привлекательностью, приятным внешним видом и поведением, полным владением обсуждаемых им вопросом, глубокими профессиональными знаниями по темам мировой цивилизации и современной геополитики, а также особенностями межкультурного взаимодействия, общения и другими аспектами. Для анализа темы были использованы методы критического анализа современных тенденций в двусторонней и многосторонней дипломатии, а также симультанного и кросс-временного исследования. Основной вывод статьи заключается в том, что для достижения успеха в профессиональной деятельности и переговорах дипломату необходимо сочетать вышеперечисленные профессиональные навыки и важные личностные качества. Кроме того, он должен уметь наилучшим образом представлять свою страну как на частных, так и на публичных встречах.
Keywords: Քաղաքագիտություն; Միջազգային հարաբերություններ